2021
DOI: 10.20473/ijosh.v10i1.2021.1-5
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Impacts of Personal Protective Equipment on Health Care Workers

Abstract: Introduction: Since the outbreak of the Ebola virus, its design has constantly been evolving to serve the purpose of protection without hampering the efficiency. In a study conducted in 2019, before the advent of COVID 19, it was found that performing precarious laboratory or clinical works while wearing PPE involved various restrictions compared to the same work without PPE.  The objective of this study is to identify the influence of personal protective equipment on physiological parameters and the individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Previous research has also noted that healthcare workers should report when they find discomfort in wearing different designs and modifications of PPE that could affect the delivery of patient care and their overall performance, such as bending, raising the arms, squatting, and walking. However, to a very rare degree they have validated the physiological changes that occur and affect the health and efficiency of workers (Arif et al, 2021).…”
Section: Discussion Related To Ppe Mapping Analysis At Hospital Xmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has also noted that healthcare workers should report when they find discomfort in wearing different designs and modifications of PPE that could affect the delivery of patient care and their overall performance, such as bending, raising the arms, squatting, and walking. However, to a very rare degree they have validated the physiological changes that occur and affect the health and efficiency of workers (Arif et al, 2021).…”
Section: Discussion Related To Ppe Mapping Analysis At Hospital Xmentioning
confidence: 99%
“…In a study that has been conducted previously, it was found that performing hazardous laboratory or clinical work while wearing Personal Protective Equipment involves various limitations compared to the same work without equipment that will protect the user. For example, the Ebola virus has led to innovations and developments in the design of equipment that will protect health workers, workers, and the general public (Arif et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Selama memberikan pelayanan Kesehatan, keselamatan perawat penting menjadi perhatian termasuk dalam hal penggunaan alat pelindung diri (APD). Penggunaan APD sangat penting untuk menjaga dan menghindari kontaminasi infeksi selama memberikan pelayanan atau disebut infeksi nosocomial atau lebih di kenal Healthcare Associated infection (HAIs) (1) Saat ini Pihak Pencegahan dan pengendalian infeksi (PPI) di rumah sakit mencanangkan untuk setiap tenaga kesehatan wajib patuh menggunakan APD saat memberikan pelayanan kesehatan. Hal tersebut dimaksudkan untuk mencegah terjadinya infeksi nosocomial di rumah sakit.…”
Section: Pendahuluanunclassified